Silicon inclusion compound electrode active material particles, electrode mixture, and lithium ion battery

By controlling the surface oxygen content and comparison area of ​​Silicon -packed Electrochemicals, the surface oxygen content and comparison area of ​​the surface of the surface, the electrode active material particles with a porous structure are prepared, solving the problem of expanding the lithium ion Improvement of battery performance.

CN119381450APending Publication Date: 2025-01-28TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410816146.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2024-06-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The expansion of the silicon inclusion electrode active material is still large during charging and needs to be further suppressed.

Method used

By controlling the surface oxygen content and comparison area of ​​the particle -activated substance particles of the silicon packet, the proportion of oxygen (wt %)/ratio of the surface area (m2/g) <0.3 of the oxygen of the surface of the 0

Benefits of technology

Effectively suppress the expansion of the electrode active material particles during charging, and improves the performance of lithium -ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004907691850000131
    Figure BDA0004907691850000131
Patent Text Reader

Abstract

The invention relates to silicon inclusion compound electrode active material particles, an electrode mixture and a lithium ion battery. This silicon inclusion compound electrode active material particle satisfies the following relational expression: 0 < surface oxygen ratio (wt%) / specific surface area (m2 / g) < 0.3. The electrode mixture of the present disclosure contains the electrode active material particles of the present disclosure. In addition, the lithium ion battery of the present disclosure has an electrode active material layer, and the electrode active material layer contains the electrode mixture of the present disclosure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to silicon inclusion compound electrode active material particles, electrode composite materials and lithium ion batteries. Background Art

[0002] In recent years, the development of batteries has been actively carried out. For example, in the automotive industry, the development of batteries used in electric vehicles or hybrid vehicles is advancing. In addition, silicon is known as an electrode active material used in batteries, especially lithium-ion batteries.

[0003] Silicon electrode active materials have a large theoretical capacity and are effective for increasing the energy density of batteries. However, silicon electrode active materials have a problem of large expansion during charging. In response to this, it is known that silicon inclusion compound electrode active materials can be used as silicon electrode active materials to suppress expansion during charging.

[0004] For example, Japanese Patent Application Laid-Open No. 2021-158003 discloses a silicon inclusion compound electrode active material having a silicon inclusion compound II type crystal phase and having Na x Si 136 (1.98<x<2.54) composition. Summary of the invention

[0005] Silicon inclusion compound electrode active materials can suppress expansion during charge compared to ordinary silicon electrode active materials, but there is still a need to further suppress expansion of silicon inclusion compound electrode active materials during charge.

[0006] An object of the present disclosure is to provide electrode active material particles that expand less during charging, and a lithium ion battery having such electrode active material particles.

[0007] The inventors of the present application have found that the above-mentioned problems can be solved by the following means.

[0008] <Scheme 1>

[0009] Silicon inclusion compound electrode active material particles satisfy the following relationship:

[0010] 0<Ratio of surface oxygen (wt%) / Specific surface area (m 2 / g)<0.3.

[0011] <Scheme 2>

[0012] The electrode active material particles according to embodiment 1 satisfy the following relationship:

[0013] 0.05≤Ratio of surface oxygen (wt%) / Specific surface area (m 2 / g)≤0.1.

[0014] <Scheme 3>

[0015] The electrode active material particle according to embodiment 1 or 2, which has a porous structure.

[0016] <Scheme 4>

[0017] An electrode composite material comprising the electrode active material particles according to any one of Embodiments 1 to 3.

[0018] <Scheme 5>

[0019] A lithium-ion battery having an electrode active material layer, wherein the electrode active material layer contains the electrode composite material described in Scheme 4.

[0020] According to the present disclosure, it is possible to provide electrode active material particles that expand less during charging and a lithium ion battery having such electrode active material particles. DETAILED DESCRIPTION

[0021] The following is a detailed description of the embodiments of the present disclosure. It should be noted that the present disclosure is not limited to the following embodiments, and can be implemented with various modifications within the scope of the disclosed gist.

[0022] 《Silicon inclusion compound electrode active material particles》

[0023] The silicon inclusion compound electrode active material particles disclosed in the present invention satisfy the following relationship:

[0024] 0<Ratio of surface oxygen (wt%) / Specific surface area (m 2 / g)<0.3.

[0025] If the surface of the silicon electrode active material particle is oxidized to become insulating silicon oxide, it is considered that the conductivity of the silicon electrode active material particle decreases. Therefore, it is preferable to prevent the surface of the silicon electrode active material particle from being oxidized as much as possible.

[0026] However, the inventors of the present application have found that when the surface of the silicon inclusion compound electrode active material particles is moderately oxidized, the fluctuation of the restraining pressure when used in a battery becomes smaller. Without being bound by any theory, it is believed that this is because when the surface of the silicon electrode active material particles is moderately oxidized, the following effects are produced. That is, it is believed that when used as a battery, the silicon oxide on the surface of the silicon electrode active material particles reacts with lithium to form lithium silicate, which has excellent ion conductivity compared to silicon oxide, and can suppress the uneven reaction between the silicon inclusion compound electrode active material particles and lithium. Moreover, since the thickness of the lithium silicate is thin, it will not excessively hinder the conduction of electrons.

[0027] It should be noted that, in the present disclosure, the “electrode active material” can be used as a “positive electrode active material” or a “negative electrode active material”, and is particularly used as a “negative electrode active material”.

[0028] Oxygen ratio on the surface (wt%) / specific surface area (m 2 / g) may be 0.01 or more, 0.03 or more, 0.05 or more, 0.06 or more, or 0.07 or more, and may be 0.25 or less, 0.20 or less, 0.15 or less, or 0.10 or less.

[0029] The proportion of oxygen on the surface of the electrode active material particles may be greater than 0wt%, greater than 0.5wt%, greater than 1.0wt%, greater than 1.5wt%, greater than 2.0wt%, greater than 2.5wt%, greater than 3.0wt%, or greater than 3.5wt%, and may be less than 30wt%, less than 25wt%, less than 20wt%, less than 15wt%, less than 10wt%, less than 8.0wt%, or less than 6.0wt%.

[0030] The method for measuring the ratio of oxygen on the surface of the electrode active material particles is not particularly limited, and examples thereof include methods of calculating the ratio of oxygen on the surface of the electrode active material particles by elemental analysis using an oxygen, nitrogen, and hydrogen analyzer, SEM-EDX, XPS, AES, etc. For example, when an oxygen, nitrogen, and hydrogen analyzer is used, EMGA-930 manufactured by Horiba, Ltd. can be used, and the ratio of oxygen can be calculated by the results of the non-dispersive infrared absorption method after the oxygen is melted.

[0031] The specific surface area of ​​the electrode active material particles can be 15m 2 / g or more, 25m 2 / g or more, 35m 2 / g or more, 45m 2 / g or above, or 50m 2 / g or above, can be 100m 2 / g or less, 90m 2 / g or less, 80m 2 / g or less, 75m 2 / g or less, or 70m 2 / g or less.

[0032] As a method for calculating the specific surface area of ​​the electrode active material particles, there is no particular limitation, and a method using the BET method can be exemplified. Specifically, the surface area can be calculated by analyzing the low-dosage adsorption method (nitrogen adsorption method) using nitrogen using the BET method. In this analysis, for example, BELSORPMAXII of MICROTRACBEL can be used.

[0033] As a method for manufacturing the electrode active material particles of the present disclosure, the following method can be exemplified, but is not limited thereto. The method comprises: mixing a silicon raw material and a sodium source and heating them to alloy them to obtain a powdered sodium silicon (NaSi) alloy; and mixing the obtained NaSi alloy and aluminum fluoride and heating them to form an inclusion compound to obtain a silicon inclusion compound.

[0034] As a sodium source in the alloying step, sodium hydride can be exemplified, but the sodium source is not limited thereto.

[0035] The heating temperature in the alloying step may be 300° C. or higher, 350° C. or higher, or 380° C. or higher, and may be 500° C. or lower, 450° C. or lower, or 420° C. or lower. In addition, the heating time may be 20 hours or higher, 30 hours or higher, or 35 hours or higher, and may be 60 hours or lower, 50 hours or lower, or 45 hours or lower.

[0036] The heating temperature in the inclusion compound formation step may be 250° C. or higher, 280° C. or higher, or 300° C. or higher, and may be 400° C. or lower, 380° C. or lower, or 350° C. or lower. In addition, the heating time may be 10 hours or higher, 15 hours or higher, or 20 hours or higher, and may be 70 hours or lower, 65 hours or lower, or 60 hours or lower.

[0037] By adjusting the heating temperature and heating time in the alloying step and the heating temperature and heating time in the inclusion formation step, the oxygen ratio and specific surface area on the surface of the silicon inclusion compound electrode active material particles can be controlled.

[0038] Furthermore, the electrode active material particles may be washed with a hydrogen fluoride solution. In this way, the oxygen ratio and specific surface area of ​​the surface of the electrode active material particles can be controlled by washing the electrode active material particles with a hydrogen fluoride solution.

[0039] The electrode active material particles of the present disclosure may have a porous structure. The porous silicon inclusion compound can absorb the expansion caused by charge and discharge by using its voids.

[0040] As a method for manufacturing the electrode active material particles of the present disclosure as porous silicon inclusion compound particles, the following method can be exemplified, but is not limited thereto. The method includes: mixing silicon and metallic lithium to obtain a lithium silicon (LiSi) alloy; reacting the obtained LiSi alloy with ethanol to obtain porous silicon; and using the obtained porous silicon as a silicon raw material to obtain a silicon inclusion compound as described above.

[0041] In this way, the specific surface area of ​​the electrode active material particles can also be controlled by making the electrode active material particles have a porous structure.

[0042] Electrode Composite Materials

[0043] The electrode composite material (electrode composite material) disclosed herein includes electrode active material particles and optionally contains a solid electrolyte, a conductive auxiliary agent, and a binder.

[0044] 〈Electrode active material particles〉

[0045] For the electrode active material particles, reference can be made to the above description related to the electrode active material particles of the present disclosure.

[0046] 〈Solid Electrolyte〉

[0047] The material of the solid electrolyte is not particularly limited, and any material available as a solid electrolyte for lithium-ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.

[0048] Examples of sulfide solid electrolytes include sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes, but are not limited to these. Specific examples of sulfide solid electrolytes include Li2S-P2S5 (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2 (Li 13 GeP3S 16 , Li 10 GeP2S 12 etc.), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x PS 6-x Cl x etc.; or combinations thereof, but not limited thereto.

[0049] The sulfide solid electrolyte may be glass or crystallized glass (glass ceramic).

[0050] 〈Conductive additives〉

[0051] The conductive additive is not particularly limited and may be, for example, VGCF (vapor grown carbon fiber), acetylene black (AB), Ketjen black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.

[0052] 〈Adhesives〉

[0053] The binder is not particularly limited, and may be, for example, polyvinylidene fluoride (PVdF), butadiene rubber (BR), styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.

[0054] Furthermore, in the present disclosure, "electrode composite material" refers to a composition that can directly constitute an electrode active material layer, or a composition that can further contain other components to constitute an electrode active material layer. In addition, in the present disclosure, "electrode composite material slurry" refers to a slurry that contains a dispersion medium in addition to the "electrode composite material" and can form an electrode active material layer by coating and drying.

[0055] Lithium-ion battery

[0056] The lithium-ion battery of the present disclosure may be a liquid battery or a solid battery. In addition, in the present disclosure, "solid battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, so a solid battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. In addition, the solid battery of the present disclosure may be an all-solid battery, that is, a battery that uses only a solid electrolyte as an electrolyte.

[0057] The lithium ion battery of the present disclosure can be constrained from both sides of the stacking direction of each layer using constraining members such as end plates. As a constraining method, a method using the constraining torque of a bolt can be exemplified, but it is not limited to this.

[0058] The lithium ion battery of the present disclosure has an electrode active material layer, and the electrode active material layer contains the electrode composite of the present disclosure. In particular, the negative electrode composite of the lithium ion battery of the present disclosure may be the electrode composite of the present disclosure. In this case, the lithium ion battery of the present disclosure may sequentially include a negative electrode collector layer, a negative electrode active material layer containing the electrode composite of the present disclosure, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode collector layer.

[0059] 〈Negative electrode current collector layer〉

[0060] The material used for the negative electrode collector layer is not particularly limited, and any material that can be used as a negative electrode collector for a battery can be appropriately used, such as copper and copper alloys, and products obtained by plating or vapor-depositing nickel, chromium, and carbon on copper, but is not limited to these.

[0061] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0062] <Negative electrode active material layer>

[0063] The negative electrode active material layer contains the electrode composite material of the present disclosure. Regarding the electrode composite material, the above description related to the electrode composite material of the present disclosure can be referred to.

[0064] Furthermore, when the negative electrode active material layer contains a solid electrolyte, the mass ratio of the electrode active material particles to the solid electrolyte in the negative electrode active material layer (mass of the electrode active material particles:mass of the solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 40:60.

[0065] The thickness of the negative electrode active material layer can be, for example, 0.1 to 1000 μm.

[0066] 〈Solid electrolyte layer〉

[0067] The solid electrolyte layer contains at least a solid electrolyte. In addition, the solid electrolyte layer may contain a binder and the like as needed in addition to the solid electrolyte. For the solid electrolyte and the binder, reference may be made to the above description related to the electrode composite material disclosed in the present invention.

[0068] The thickness of the solid electrolyte layer is, for example, 0.1 to 300 μm, or preferably 0.1 to 100 μm.

[0069] <Positive electrode active material layer>

[0070] The positive electrode active material layer is a layer containing a positive electrode active material and, optionally, a solid electrolyte, a conductive auxiliary agent, a binder, a thickening agent, and the like.

[0071] There is no particular limitation on the material of the positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, by Li 1+x Mn 2-x-y M y O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni and Zn) is a heterogeneous element substituted Li-Mn spinel, lithium titanate (Li x TiO y ), lithium metal phosphate (LiMPO4, M is one or more metals selected from Fe, Mn, Co and Ni), etc., but is not limited to these.

[0072] The positive electrode active material may have a coating layer. The coating layer is a layer containing a material having lithium ion conductivity, low reactivity with the positive electrode active material and the solid electrolyte, and a coating layer that can maintain a non-flowing state even when in contact with the active material or the solid electrolyte. Specific examples of materials constituting the coating layer include LiNbO3, Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.

[0073] The shape of the positive electrode active material may be, for example, a particle shape. The average particle size (D50) of the positive electrode active material is not particularly limited, and may be, for example, 10 nm or more, or 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material may be, for example, 50 μm or less, or 20 μm or less. The average particle size (D50) may be calculated, for example, by measurement using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).

[0074] For the solid electrolyte, the conductive auxiliary agent and the binder, reference can be made to the above description related to the electrode composite material of the present disclosure.

[0075] When the positive electrode active material layer contains a solid electrolyte, the mass ratio of the positive electrode active material to the solid electrolyte (mass of the positive electrode active material:mass of the solid electrolyte) in the positive electrode active material layer is preferably 85:15 to 30:70, more preferably 80:20 to 50:50.

[0076] The thickness of the positive electrode active material layer is, for example, 0.1 μm to 1000 μm, preferably 1 μm to 100 μm, and more preferably 30 μm to 100 μm.

[0077] 〈Positive electrode current collector layer〉

[0078] There is no particular limitation on the material used in the positive electrode collector layer. Materials that can be used as positive electrode collectors for batteries can be appropriately used, such as SUS, nickel, chromium, gold, platinum, aluminum, iron, titanium and zinc, as well as products obtained by plating or vapor-depositing nickel, chromium, carbon, etc. on these metals, but are not limited to these.

[0079] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0080] 《Example 1》

[0081] 〈Synthesis of Silicon Inclusion Compound Electrode Active Material Particles〉

[0082] (porous)

[0083] As a silicon (Si) source, Si powder (High Purity Science, SIEPB32) was prepared. Metallic lithium (Li) and the Si powder were weighed so that the molar ratio was Li:Si=4:1, and the weighed Li and Si powders were mixed in a mortar under an argon atmosphere at room temperature for 0.5 hours to react, thereby obtaining lithium silicon (Li4Si). The obtained Li4Si was reacted with ethanol in an argon atmosphere. Furthermore, the reaction product was washed with a 3wt% hydrogen fluoride (HF) solution, filtered, and the filtered and separated solid component was dried at 120°C for more than 3 hours to obtain Si powder with a porous structure.

[0084] (Alloying)

[0085] A sodium silicon (NaSi) alloy was manufactured using Si powder having a porous structure and sodium hydride (NaH) as a sodium (Na) source. As NaH, NaH previously washed with hexane was used. NaH and Si powder having a porous structure were weighed so that the molar ratio was 1.05:1, and the weighed NaH and Si powder having a porous structure were mixed with a cutting mill. The obtained mixture was heated in a heating furnace under an argon atmosphere at 400°C for 40 hours to obtain a powdered NaSi alloy.

[0086] (Inclusion Compound)

[0087] The obtained NaSi alloy and aluminum fluoride (AlF3) particles were weighed so that the molar ratio was 1:0.35, and the weighed NaSi alloy and AlF3 particles were mixed with a cutter to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction container, and heated in an argon atmosphere in a heating furnace at 345°C for 40 hours to react, thereby obtaining a silicon inclusion compound. The obtained silicon inclusion compound was acid-washed using a mixed solvent prepared by mixing HNO3 and H2O in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, it was filtered, and the filtered and separated solid component was dried at 120°C for more than 3 hours to obtain silicon inclusion compound electrode active material particles with a porous structure.

[0088] 《Example 2》

[0089] Silicon inclusion compound electrode active material particles having a porous structure were obtained by the same operation as in Example 1, except that the particles were heated at 345°C for 60 hours during the inclusion compound formation, and after acid washing, subsequent filtration and drying, they were further washed with a 3wt% HF solution, filtered, and dried at 120°C for more than 3 hours.

[0090] 《Example 3》

[0091] Silicon inclusion compound electrode active material particles having a porous structure were obtained in the same manner as in Example 2 except that heating was performed at 335° C. for 60 hours during inclusion compound formation.

[0092] 《Example 4》

[0093] Silicon inclusion compound electrode active material particles having a porous structure were obtained in the same manner as in Example 2 except that heating was performed at 325° C. for 60 hours during inclusion compound formation.

[0094] 《Example 5》

[0095] Silicon inclusion compound electrode active material particles having a porous structure were obtained in the same manner as in Example 2 except that heating was performed at 345° C. for 40 hours during inclusion compound formation.

[0096] Example 6

[0097] Silicon inclusion compound electrode active material particles having a porous structure were obtained in the same manner as in Example 2 except that heating was performed at 345° C. for 20 hours during inclusion compound formation.

[0098] 《Example 7》

[0099] (Alloying)

[0100] Sodium silicon (NaSi) alloy was manufactured using Si powder (High Purity Science, SIEPB32) and sodium hydride (NaH) as a sodium (Na) source. As NaH, NaH previously washed with hexane was used. NaH and Si powder having a porous structure were weighed so that the molar ratio was 1.05:1, and the weighed NaH and Si powder were mixed with a cutting mill. The obtained mixture was heated in a heating furnace under an argon atmosphere at 400°C for 40 hours to obtain a powdered NaSi alloy.

[0101] (Inclusion Compound)

[0102] The obtained NaSi alloy and aluminum fluoride (AlF3) particles were weighed so that the molar ratio was 1:0.35, and the weighed NaSi alloy and AlF3 particles were mixed with a cutter to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction container, and heated in an argon atmosphere in a heating furnace at 345°C for 40 hours to react, thereby obtaining a silicon inclusion compound. The obtained silicon inclusion compound was acid-washed using a mixed solvent of HNO3 and H2O in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, it was filtered, and the solid component separated by filtration was dried at 120°C for more than 3 hours. Furthermore, the obtained silicon inclusion compound was washed with a 3wt% HF solution, filtered, and dried at 120°C for more than 3 hours to obtain silicon inclusion compound particles.

[0103] (porous)

[0104] Li and the obtained silicon inclusion compound particles were weighed so as to have a molar ratio of 2.5:1, and the weighed Li and Si powders were mixed in a mortar under an argon atmosphere at room temperature for 0.5 hours to react, thereby obtaining lithium silicon (Li 2.5 Si). Make the obtained Li 2.5 Si reacted with ethanol in an argon atmosphere, thereby obtaining silicon inclusion compound electrode active material particles having a porous structure.

[0105] Comparative Example 1

[0106] Silicon clathrate electrode active material particles of Comparative Example 1 were obtained in the same manner as in Example 2 except that Si powder (High Purity Scientific, SIEPB32) was used in alloying instead of Si powder having a porous structure.

[0107] Furthermore, the surface of the electrode active material particles in the above-mentioned examples may contain a film or impurities containing O element, C element, N element, etc.

[0108] 〈Manufacturing of lithium-ion batteries〉

[0109] (Preparation of negative electrode composite material)

[0110] In a polypropylene container, butyl butyrate, a 5wt% butyl butyrate solution of a polyvinylidene fluoride (PVDF)-based binder, vapor-phase carbon fiber (VGCF) as a conductive aid, electrode active material particles of each example, and Li2S-P2S5-based glass ceramics as a sulfide solid electrolyte were added, and stirred for 30 seconds using an ultrasonic dispersion device (UH-50 made by SMT). Next, the container was vibrated for 30 minutes using a vibrator (TTM-1 made by Shibata Science Co., Ltd.) to obtain a slurry-like negative electrode composite (negative electrode composite slurry).

[0111] (Formation of Negative Electrode Active Material Layer)

[0112] The obtained negative electrode composite slurry was applied onto a copper (Cu) foil as a negative electrode current collector layer using a coater by a doctor blade method, and dried on a hot plate heated to 100° C. for 30 minutes to form a negative electrode active material layer on the negative electrode current collector layer.

[0113] (Formation of Solid Electrolyte Layer)

[0114] Heptane, a 5 wt% heptane solution of a butene rubber (BR)-based binder, and Li2S-P2S5-based glass ceramics as a sulfide solid electrolyte were added to a polypropylene container and stirred for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT). Next, the container was vibrated for 30 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.) to obtain a solid electrolyte slurry.

[0115] The obtained solid electrolyte slurry was applied onto an aluminum (Al) foil as a release sheet using a coater by a doctor blade method, and dried on a hot plate heated to 100° C. for 30 minutes to form a solid electrolyte layer. A plurality of solid electrolyte layers were produced.

[0116] (Preparation of positive electrode composite material)

[0117] In a polypropylene container, butyl butyrate, a 5 wt % butyl butyrate solution of a PVDF-based binder, and LiNi 2000 with an average particle size of 6 μm as a positive electrode active material were added. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2S-P2S5 glass ceramics as sulfide solid electrolyte, and VGCF as conductive additive were stirred for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT). Next, the container was vibrated for 3 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.), and then stirred for 30 seconds using an ultrasonic dispersion device, and vibrated for 3 minutes using a vibrator to obtain a slurry-like positive electrode composite material (positive electrode composite material slurry).

[0118] (Formation of Positive Electrode Active Material Layer)

[0119] The obtained positive electrode composite slurry was applied onto an Al foil as a positive electrode collector layer using a doctor blade method using a coater, and dried on a hot plate heated to 100° C. for 30 minutes to form a positive electrode active material layer on the positive electrode collector layer.

[0120] (Battery Assembly)

[0121] The positive electrode current collector layer, the positive electrode active material layer, and the first solid electrolyte layer were stacked in this order, and the stack was placed in a roll press and pressed at a pressing pressure of 100 kN / cm and a pressing temperature of 165° C., thereby obtaining a positive electrode stack.

[0122] The negative electrode current collector layer, the negative electrode active material layer, and the second solid electrolyte layer were stacked in this order, and the stack was placed in a roll press and pressed at a pressing pressure of 60 kN / cm and a pressing temperature of 25° C., thereby obtaining a negative electrode stack.

[0123] Furthermore, the Al foil as a release sheet was released from the surfaces of the solid electrolyte layers of the positive electrode stack and the negative electrode stack. Next, the Al foil as a release sheet was released from the third solid electrolyte layer.

[0124] The positive electrode stack and the negative electrode stack were stacked one on top of the other in such a way that the solid electrolyte layer side of each of them was opposite to the third solid electrolyte layer, and the stack was placed in a flat uniaxial press and pre-pressed at 100 MPa and 25° C. for 10 seconds, and finally the stack was placed in a flat uniaxial press and pressed at a pressing pressure of 200 MPa and a pressing temperature of 120° C. for 1 minute. Thus, an all-solid-state battery was obtained.

[0125] "evaluate"

[0126] 〈Surface oxygen ratio〉

[0127] The oxygen ratio on the surface of the electrode active material particles was calculated from the results of measurement by a non-dispersive infrared absorption method after melting with oxygen using an oxygen, nitrogen, and hydrogen analyzer (EMGA-930 manufactured by Horiba, Ltd.).

[0128] 〈Specific surface area〉

[0129] The specific surface area of ​​the electrode active material particles was calculated by analyzing the surface area measured by a low-dosage adsorption method (nitrogen adsorption method) using the BET method. The analysis was performed using BELSORPMAXII manufactured by MICROTRACBEL.

[0130] <Determination of the increase in restraint pressure>

[0131] The manufactured battery cell was constrained with a specified constraining pressure using a constraining fixture, and the increase in the constraining pressure when charged to 4.55V at a constant current-constant voltage for 10 hours (1 / 10C) was measured. A large increase in the constraining pressure means a large amount of expansion of the active material. It should be noted that the increase in the constraining pressure is the difference between the highest and lowest values ​​of the constraining pressure, and the value of the embodiment is a relative value when the value of Comparative Example 1 is set to 100.

[0132] "result"

[0133] The surface oxygen ratio and specific surface area of ​​the electrode active material particles were measured, and the surface oxygen ratio (wt %) / specific surface area (m 2 Table 1 shows the values ​​of MgO / g) and the measurement results of the increase in the restraint pressure.

[0134]

Table 1

[0135]

[0136] As shown in Table 1, the ratio of oxygen contained on the surface (wt%) / specific surface area (m 2 The battery of the example having the electrode active material particles within the range of the present disclosure (g) was smaller than the battery of the comparative example in terms of the increase in confinement pressure.

Claims

1. Silicon inclusion compound electrode active material particles satisfying the following relationship: 0<Ratio of surface oxygen (wt%) / Specific surface area (m 2 / g)<0.

3.

2. The electrode active material particle according to claim 1, which satisfies the following relationship: 0.05≤Ratio of surface oxygen (wt%) / Specific surface area (m 2 / g)≤0.

1. The electrode active material particle according to claim 1 or 2, which has a porous structure.

4. An electrode composite material comprising the electrode active material particles according to claim 1 or 3.

5. A lithium ion battery comprising an electrode active material layer, wherein the electrode active material layer contains the electrode composite material according to claim 4.

Citation Information

Patent Citations

  • Active material, negative electrode layer, battery and these manufacturing methods

    JP2021158003A